Studi Kasus Deskripsi Asuhan Keperawatan Gangguan Rasa Nyaman Nyeri Pada Pasien Yang Mengalami Gangguan Sistem Reproduksi di Rumah Sakit Wilayah Jakarta - Rahmawati, Agustini Liviana Dwi; Sari, Ema Laila (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Disorders of the female reproductive system can occur due to various risk factor, one of which is abnormal cell growth. Abnormal cells that occur depending on the location and can spread if accompanied by malignan, this condition can cause discomfort that affects patients who experience pain, so nursing care is needed so that these conditions do not affect the impact and quality of life of patients. The aim is to provide nursing care to patients with reproductive disorders who experience discomfort and pain. This scientific writing method uses a case study method with an analytical descriptive study design. This method is used to describe and analyze 2nd patients, with a holistic approach to nursing care. This case study was conducted in one of the hospitals in the Jakarta area, and set the inclusion criteria for the subjects to be used. The author chose 2nd patients, namely patients with reproductive disorders with postoperative endometriosis and ovarian cancer who experienced discomfort and pain. Nursing care is carried out for 3x24 hours starting from assessment to documentation. Results: In Mrs. N and Mrs. I, the pain was felt in the postoperative area and the pain was partially resolved, but the patient was able to control the pain he felt. In Mrs. N and Mrs. I, the pain scale on the first day was a scale of 5 and a scale of 4, on the second day a scale of 3rd and a scale of 3rd, on the third day a scale of 0 and a scale of 1st after collaboration between analgesics and non-pharmacological therapy of musical distraction. Conclusion: In reproductive disorders patients who experience pain there is the ability to control pain in nursing care provided by nurse.